Integrasi Taʿabbudī dan Taʿaqqulī melalui Ḥīlah Syarʿiyyah dalam Ilmu Falak: Kontribusi pada Maqāṣid al-Sharīʿah - Muchammad Azkal Huda; Inayah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Islamic astronomy (ilmu falak) as a multidisciplinary field in Islam integrates science, jurisprudence, and theology, particularly in time-based worship such as determining the beginning of the lunar month, qibla direction, and prayer times. This study examines the application of the concept of ḥīlah syarʿiyyah (Sharia-endorsed legal stratagem) in the dimensions of Islamic astronomy, focusing on three research questions: the concept and classification of hilah, scholars' views based on maqāṣid al-sharīʿah, and its implementation in determining the lunar month, qibla direction, and prayer times. Employing a library research method with a descriptive-analytical approach, data were collected from primary sources (classical fiqh books) and secondary sources (reputable journals 2021–2026) through documentary study, then analyzed using the Miles, Huberman, and Saldaña interactive model. The findings reveal that hilah is classified into masyruʿah (permissible) and mamnuʿah (prohibited) based on its objectives; scholars' views are divided into three positions (permissible with strict conditions, absolutely prohibited, and dependent on intention/context), all of which use maqāṣid as the main parameter; and the implementation of hilah in Islamic astronomy—through the use of hisab imkān al-rukyat (MABIMS criteria), modern technology for qibla correction (Google Earth, Qibla Tracker), and astronomical data for prayer times—constitutes a legitimate masyruʿah hilah because it aims to maintain certainty and perfection of worship. This study contributes to the development of an integrative taʿabbudī-taʿaqqulī framework and provides legitimacy for global Islamic calendar unification policies